(untitled) (Annals of Medical Research, 2023)
Aim: The aim of this study was to determine the anticancer activity of royal jelly (RJ) and Aloe vera (AVE) separately and in combination on human non-small cell lung cancer (A549) and colorectal adenocarcinoma cells (HT29) and to investigate whether the side effects of AVE can be ameliorated by RJ. Materials and Methods: The antiproliferative activity of RJ, AVE, and the combination of AVE and RJ was performed in vitro on A549 and HT29 cells using a Real-Time Cell Analyzer (xCELLigence). To determine the mechanisms underlying the antiproliferative activity, cell apoptosis was performed by flow cytometry using the annexin V-FITC/PI apoptosis detection kit, while cell migration was determined by wound healing assay. Results: Treatment with varying concentrations of AVE, RJ, and the combination of AVE and RJ was concluded to have dose-dependent antiproliferative activity and that the AVE-RJ combination induced 41% of HT29 and 11.79% of A549 early apoptosis (p<0.05). However, the inhibition effect of the combination of AVE and RJ on cancer cell migration was not detected. Conclusion: Taken together, our results showed that the AVE-RJ combination could be a promising therapeutic combination in A549 and HT29 by inducing apoptosis. The obtained results revealed that the AVE (40 µg/mL) and RJ (300 mg/mL) combination in the A549 cell line exhibited earlier antiproliferative activity than the 40 µg/mL AVE. Also, it has been found that the antiproliferative activity of AVE is enhanced when used in combination with RJ.